Hydrophobicity-tuned anion responsiveness underlies endosomolytic cargo delivery mediated by amphipathic vehicle peptides - Chen, Xiaolong; Liu, Hanjie; Li, Ang; Ji, Shuangshuang; Fei, Hao (The Journal of biological chemistry, 2021)
Peptide conformation can change subject to environment cues. This concept also applies to many cationic amphipathic peptides (CAPs) known to have cell membrane lytic or penetrative activities. Well-conditioned CAPs can match the properties of the target membrane to support their intended biological functions, e.g., intracellular cargo delivery; however, the intricacy in such conditioning surpasses our current understanding. Here we focused on hydrophobicity, a key biophysical property that dictates the membrane activity of CAPs, and applied a structure–function strategy to evolve a template peptide for endosomolytic cargo delivery. The template was subjected to iterative adjustment to balance hydrophobicity between its N-terminal linear and C-terminal helical domains. We demonstrate that the obtained peptide, LP6, could dramatically promote cargo cell entry and facilitate cytosolic delivery of biomacromolecules such as FITC-dextran, saporin, and human IgG. Among the evolved peptide series, LP6 has low cytotoxicity and moderate hydrophobicity, exhibits maximum change in helical conformation in response to negatively charged phospholipids, and also shows an apparent aggregational behavior in response to sialic acid enrichment. These attributes of LP6 collectively indicate that its anion-responsive conformational change is a critical underlining of its endosomolytic cargo delivery capability. Our results also suggest that modulation of hydrophobicity serves as a key to the precise tuning of CAP's membrane activity for future biomedical applications.